Pentingnya Kepatuhan Minum Obat Mengontrol Tekanan Darah Penderita Hipertensi - Kartika; Syamsul Idris (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Blood pressure in hypertensive patients must be controlled to prevent life-threatening complications. Blood pressure control can be done with pharmacological therapy. Pharmacological therapy is therapy using antihypertensive drugs. Antihypertensive drugs have been clinically proven to reduce the risk of cardiovascular events and death in hypertensive patients. In Tanjung Gusta Village, Medan City, it was identified that hypertensive patients were not compliant with taking their medication. The purpose of this community service was to raise awareness among hypertensive patients regarding medication compliance so that their disease remains under control. This community service used lecture and question and answer methods. From this community service activity, it was found that compliance with taking hypertension medication in hypertensive patients was relatively low, with 18 people (46.2%) with the hypertension category experienced by the majority of Stage I Hypertension, with 18 people (46.2%). It is hoped that the results of this community service can be used as input for the local community health center to provide education to support medication compliance in essential hypertension patients to prevent complications.